Keefektifan Pembuatan RPP Inovatif, Media dan Weblog Pembelajaran guna meningkatkan Kualitas Pembelajaran di Pondok Pesantren Darussalam - Muhammad Jhoni (Jurnal Ilmu Fisika dan Pembelajarannya (JIFP), 2022)
The purpose of this service program is to assist madrasa teachers at the Darussalam Islamic boarding school in making Innovative RPP, Learning Media, and Web blogs. The method used is Participatory Action Research (PAR), in which all relevant parties are actively involved in analyzing the stages of ongoing activities in order to make changes for the better. Based on the results of the service, it was found that the average attitude of the teacher was 6.38 for making weblogs, an average of 7.54 for PPT, and an average of 6.97 for RPP, each of which was in the good category.; 86% of the 37 participants were able to make weblogs, PPT, and RPP; each school makes an official school weblog. Thus, it can be concluded that this PKM activity has a good impact on madrasa teachers at the Darusaalam Islamic Boarding School.